Haze types in Beijing and the influence of agricultural biomass burning - W. J. Li; L. Y. Shao; P. R. Buseck (Atmospheric Chemistry and Physics, 2010)
Emissions from agricultural biomass burning (ABB) in northern China have a significant impact on the regional and global climate. The monthly average aerosol optical depth (AOD) at 550 nm in northern China in 2007 had a maximum of 0.7 in June. The AOD measurements are consistent with regional brown hazes that occurred at that time, which was a period of severe aerosol pollution. Aerosol particles were collected in urban Beijing from 12 to 30 June 2007, during a period of high haze, and studied using transmission electron microscopy with energy-dispersive X-ray spectrometry. The dominant particle types collected in the fine fraction (diameter <1 μm) were ammonium sulfate, soot, K2SO4, KNO3, and organic matter, except that the K salts were minor between 21 and 30 June. K-rich particles as tracers of biomass burning, together with wildfire maps, show that intense regional ABB in northern China contributed significantly to the regional haze between 12 and 20 June. We therefore grouped the episodes into type-1 and -2 haze, with the former occurring between 12 and 20 June and the latter between 21 and 30 June. After long-range transport, ABB particles in the type-1 haze exhibited marked changes in morphology, composition, and mixing state. KCl particles were absent, presumably having been converted by heterogeneous reactions to K2SO4 and KNO3. Soot particles were mixed with the other particle types. Abundant organic matter and soluble salts emitted by ABB increased their sizes during transport and resulted in more hygroscopic aerosol particles in downwind areas, becoming additional cloud condensation nuclei. The high AOD (average value 2.2) in Beijing during 12 to 20 June is partly explained by the hygroscopic growth of fine aerosol particles and by the strong absorption of internally mixed soot particles, both coming from regional ABB emissions. Therefore, it is important to consider the origins of the haze, which in turn leads to the different particle types.